Invasion from the South: Social Construction of the Haitian ‘Other’ in The Bahamas - Perry, Charmane M. (International Journal of Bahamian Studies, 2014)
Since 1957, the Bahamian government has been trying to control the migration of undocumented Haitians to and their movement through The Bahamas. Due to the continued and incessant migration and the question of citizenship for Haitians, Bahamians have come to perceive Haitians as a threat to the national and cultural sovereignty of The Bahamas. The media, government policies, and everyday constructions of Bahamian identity have played a significant role in socially constructing the image and status of Haitians residing in The Bahamas. The perception and internalization of these images and ideas have resulted in the denial of human rights for Haitians and people of Haitian descent residing in The Bahamas.